Direct Measurement of Glyconanoparticles and Lectin Interactions by Isothermal Titration Calorimetry - Wang, Xin (2012)
Glyconanomaterials have shown high potential in applications including bioanalysis and nanomedicine. Here, a quantitative analytical technique, based on isothermal titration calorimetry, was developed to characterize the interactions between glyconanoparticles and lectins. By titrating lectins into the glyconanoparticle solution, the apparent dissociation constant, thermodynamic parameters, and the number of binding sites were derived simultaneously. For the glyconanoparticles-lectin binding pairs investigated, a 3–5 orders of magnitude affinity enhancement over the free ligand-lectin interactions was observed which can be attributed to the multivalent ligand presentation on the nanoparticles. The impact of ligand density was also studied, and results showed that the affinity increased with the number of glycans on the nanoparticle.